Realities and prospects of managing the development of agricultural business in Ukraine - Shmatkovska, Tetiana; Agres, Oksana; Luchechko, Yurii; Korobchuk, Liudmila; Naumenko, Nataliia; Voichuk, Maksym; Dziamulych, Mykola (University of Agricultural Sciences and Veterinary Medicine Bucharest Romania. Faculty of Management and Rural Development, 2023)
The world`s food security largely depends on the stability of agri-business worldwide, but mainly in the main producing countries of agri-food products. The purpose of the study is to determine the current realities and opportunities for the development of agrarian business in Ukraine in crisis conditions for the development of effective strategies and promising growth of the agrarian sector. Research methods: monographic, abstract-logical methods, method of analogies and comparisons, systematic approach, statistical and graphic methods. In the course of the study, it was determined that in 2022, a significant number of agricultural enterprises suffered losses as a result of the system challenges. The loss of 15-20% of cattle, pigs, and poultry, and the loss of production facilities and animal husbandry complexes led to a reduction in production in both the crop and animal husbandry sectors. The article highlights the exogenous and endogenous risks of the functioning of the agricultural sector. Internal risks include loss of production and resource potential of the agricultural sector; the liquidation of a significant number of agrarian business enterprises; change of specialization due to significant economic losses; loss of part of the infrastructure facilities for storage and primary processing of agricultural products; difficulty in selling products to foreign markets. Exogenous risks are described, in particular, the reduction of investments in agricultural production, problems with the purchase and import of fertilizers and plant protection products into the country, and delays in the purchase of modern agricultural machinery. It was noted that the presence of the listed external risks will have a negative impact on the country`s economy and food security. The actions of the government for the sustainability of agrarian business are described, namely, the restoration of the export of agricultural products by sea, the development of alternative logistics networks for export, solving the problems of the seed company, and providing the possibility of special credit programs and tax holidays. The main problematic issues that the government needs to solve to ensure the stability of the agrarian business and the possibility of its further effective functioning are presented.
Keywords: agrarian business; risks; tax holidays; sustainable development; innovative entrepreneurship; preferential lending